Trait anxiety negatively modulates the coupling of motor event-related desynchronization and event-related synchronization - Chia-Hsiung Cheng; Pei-Ying S. Chan; Si-Yu Chen; Yu-Han Chen; Hsinjie Lu; Chia-Yih Liu (BMC Psychiatry)
Abstract Background Recent neurophysiological studies showed that patients with psychiatric disorders demonstrated abnormalities in sensorimotor functions in addition to cognitive deficits. These findings intrigued us to investigate whether trait anxiety, a persistent inclination towards being anxious in multiple contexts, would affect motor cortical functions. Event-related desynchronization (ERD) and event-related synchronization (ERS) of α and β oscillations are associated with movement execution and movement termination, respectively. However, no study has comprehensively examined the effects of trait anxiety on motor ERD and ERS. Therefore, this study aimed to determine how trait anxiety influences these motor cortical oscillations. Methods Twenty subjects (top 10% of the trait anxiety score distribution from 400 college students) with higher trait anxiety (HTA) and 20 subjects (bottom 10% of trait anxiety score distribution from the same sample) with lower trait anxiety (LTA) were recruited to perform a Go-Nogo task during electroencephalographic recordings. ERD and ERS of α and β oscillations to Go responses were compared between these two groups. The associations between ERD and ERS in each group were also examined. Results Neither ERD nor ERS power changes were significantly different between LTA and HTA groups. Interestingly, a significant correlation between β ERD and α ERS/β ERS was found in the individuals with LTA; however, such functional coupling was not present in the individuals with HTA. Conclusion Trait anxiety negatively modulates the coupling of motor ERD and ERS.